Nature and Extent of COVID-19 Challenges Among Small, Medium, and Micro Enterprises in Botswana. - PEARSON CHAURURA (Rescollacom (Research Collaborations Community), 2025)
Small, Medium, and Micro Enterprises (SMMEs) make significant contribution to economic growth in both developed and developing economies. In Botswana, the government has made extensive investment in the SMME sector, but the expected returns are compromised by poor performance and business failure among SMMEs. This problem is amplified during crises as they bring various challenges to the sector. This study used the recent COVID-19 pandemic as a proxy to identify and evaluate the nature and extent of challenges faced by SMMEs in Botswana during crisis times. A mixed methods approach was employed to collect data from 250 SMMEs in Gaborone, Francistown and surrounding areas. SPSS and manual coding and thematic analysis were used to analyse the data. It was found that SMMEs in Botswana encountered several challenges the most important being financial (75.4%), technological (74.4%), and human resource (68.8%) challenges. Specifically, these were drop in sales/business (89.2%), need for accelerated digitisation (45.8%), and capacity to ensure the well-being of employees (58.4%). Additionally, there were challenges with accessing and utilising government programmes despite a high level of awareness among SMMEs. Some challenges showed significant association with SMME industry sectors implying their potential importance in some sectors compared to others. The dominance of financial, technological, and human resource challenges may underscore the central role they play in SMME operations. It is not enough for governments to avail resources, programmes, policies and frameworks in support of SMMEs. More needs to be done to promote their access, uptake, and utilisation.